Femicide and COVID-19 Pandemic: Examining the Situation in Croatia, Hungary, Montenegro, North Macedonia, and Slovenia - Hacin, Rok (Journal of contemporary criminal justice, 2024)
Government measures to limit the spread of COVID-19 affected crime opportunities and criminal justice systems, resulting in changes in crime trends. This article explores the effects of restrictions (lockdowns) on the number of femicides. The monthly data on femicides from 2017 to 2021 were collected in five Central and South-eastern European countries: Croatia, Hungary, Montenegro, North Macedonia, and Slovenia. The total number of femicides from 2017 to 2021 decreased in all observed countries. Increases were detected in Croatia and Slovenia in 2020. However, they presented an exception to the general trend. The monthly distribution of femicides showed that there was no common point peak month(s) among observed countries. Analyzing the effects of the level of restrictions using the Stringency Index on the number of femicides confirmed the initial observation that the number of femicides was not dependent on lockdown measures. In general, the findings show that restriction measures had no effect on the number of femicides in the studied countries.